Identification of a novel METTL23 gene variant in a patient with an intellectual development disorder: a literature review and case report - Zha, Jian; Chen, Yong; Cao, Fangfang; Yu, Yanghong; Wang, Ruiyan; Zhong, Jianmin (Frontiers in Pediatrics, 2024)
METTL23 belongs to a family of protein lysine methyltransferases that methylate nonhistone proteins. Recently, the METTL23 gene has been reported to be related to intellectual developmental disorder, autosomal recessive 44. Patients present with developmental delay, intellectual disability (ID), and variable dysmorphic features. Here, we report a Chinese girl who presented with global developmental delay, abnormal brain structure, and multiple facial deformities including a short/upturned nose with a sunken bridge, thin lips, and flat occiput. Whole exome sequencing identifies a novel variant (NM_001080510.5: c.322+1del) on the METTL23 gene. This variant is not collected on public human variants databases such as gnomAD, predicted to influence the splicing as a classical splicing variant, and classified as Pathogenic according to American College of Medical Genetics and Genomics (ACMG) guidelines. Since patients with METTL23 related ID are rare, we summarize and compare the clinical phenotype of reported patients with METTL23 variants. Our report further expands the METTL23 variants and provides new evidence for clinical diagnosis of METTL23 related ID.